The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5713/ajas.2009.80649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Source of Supplemental Zinc on Performance, Nutrient Digestibility and Plasma Mineral Profile in Cashmere Goats

Abstract: This experiment was designed to evaluate the effects of source of supplemental zinc (Zn) on performance, nutrient digestibility and plasma mineral profile in Cashmere goats during the cashmere fiber growing period. Twenty-seven Liao Ning Cashmere wether goats (9-10 month of age; initial BW = 19.31±0.32 kg) were fed a basal diet (containing 22.3 mg Zn/kg DM) with no supplemental Zn (control) or 20 mg of supplemental Zn/kg of DM from Zn sulfate (ZnSO 4 ) or Zn methionine (ZnMet) for 60 days including a 10-day me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
7
12
1
3
Order By: Relevance
“…This may be because Zn tends to selectively inhibit growth, or metabolic activities, of rumen microbes [12]. Salama Ahmed et al [15] and Jia et al [13,14] found no differences in the digestibility of DM, CP, NDF, and ADF in goats supplemented with Zn, which does not agree with our findings that Zn supplementation increased IVDMD compared to the control. Moreover, adding Zn in combination with Cu, and separately, decreased IVDMD.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This may be because Zn tends to selectively inhibit growth, or metabolic activities, of rumen microbes [12]. Salama Ahmed et al [15] and Jia et al [13,14] found no differences in the digestibility of DM, CP, NDF, and ADF in goats supplemented with Zn, which does not agree with our findings that Zn supplementation increased IVDMD compared to the control. Moreover, adding Zn in combination with Cu, and separately, decreased IVDMD.…”
Section: Discussioncontrasting
confidence: 81%
“…For example, adding 10, 20, and 30 mg Cu/kg dry matter (DM) to ruminant diets did not affect digestibility of DM, crude protein (CP), and acid detergent fiber (ADF) in Cashmere goats [9,10], while the intra-ruminal administration of boluses containing 8.65 mg Cu/kg DM reduced apparent digestibility of neutral detergent fiber (NDF) and CP in growing heifers [11]. Research to determine the effects of Zn supplementation on digestibility of nutrients is also still limited and inconclusive [12][13][14]. Supplementation of 1 g/day with organic Zn in diets fed to dairy goats increased the digestibility of DM, organic matter, and CP [15].…”
Section: Introductionmentioning
confidence: 97%
“…The average body weight gain of goat on the whole treatments was around 52-65g and categorized into moderate. Jia et al (2009) fed Z-methionine on goat by 20 ppm and resulted daily weight gain by 42.7 kg. Znmethionine supplementation on lamb as much as 30 and 60 ppm resulted in daily weight gain each by 45 g and 55 g (Haryanto et al 2005).…”
Section: Feed Consumption and Body Weight Gainmentioning
confidence: 99%
“…Inorganic Zn in the form of oxide zinc (ZnO) or sulfate zinc (ZnSO4) has been used as supplement for ruminant and those two inorganic zincs forms were reported having relatively comparable with the availability level (Jia et al 2009;Jia et al 2008). Organic Zn in the form of Zn-methionine as methyl (CH3) contributor is important in the DNA transcription and translation process.…”
Section: Introductionmentioning
confidence: 99%
“…higher in Zn-meth group as compared to control group. Jia et al (2009) reported that Zn supplementation had influence on digestibility of DM, CP, EE and NDF (P>0.05). Moreover, ADF digestibility in the group supplemented with ZnMet was significantly higher than in other treatments (P<0.05).…”
Section: Body Weight Gainmentioning
confidence: 96%